Review of case law 2th Chamber of the Supreme Court - Reyes López, Javier Ignacio (Logos Guardia Civil, Scientific Magazine of the University Center of the Guardia Civil, 2024)
1. Supreme Court Ruling 653/2023, of 20 September 2023. Attempted murder. Civil Guard officers injured. Difference between animus necandi and leadendi. 2. Supreme Court Ruling 685/2023, of September 2023. Perpetration of and complicity in crimes against public health. Completion and attempt. 3. Supreme Court Ruling 648/2023, of 27 July 2023. Dissemination of child pornography with particularly degrading facts. 4. Supreme Court Ruling 614/2023, of 14 July. Validity of direct police surveillance and the use of photographs in private spaces. 5. Supreme Court Ruling 576/2023, of 10 July. Police intervention without a qualified interpreter for emergency reasons. Evidentiary validity. 6. Supreme Court Ruling 628/2023, of 19 July. Damage caused by graffiti on a railway. 7. STS 693/2023, of 27 September. Offence of disclosure of secrets. Disclosure of images without the victim’s consent. 8. Supreme Court Ruling 647/2023, of 27 July. Offence against sexual indemnity committed by a physiotherapist. Interpretation of the victim’s consent. Effectiveness of reporting and willingness to report. 9. Supreme Court Ruling 624/2023 of 18 July 2023. Thwarted malice aforethought and cohabitative malice aforethought. 10. Constitutional Court Ruling 92/2023, of 11 September. Police capture of images in communal garages without judicial authorisation. 11. Supreme Court Ruling 750/2023, of 11 October. Cultivation of marijuana. Forms of participation. Commission by omission does not apply. 12. Constitutional Court Ruling 68/2023 of 19 June. Infringement of the right of the person under investigation to information on the facts with which he is charged and access to the proceedings, as statements of the right of defence, when the case is under investigation secrecy.